Pengaruh Klimat terhadap Infeksi Nematoda Saluran Pencernaan pada Sapi Potong di Kabupaten Bojonegoro, Provinsi Jawa Timur - Aji Winarso; Fadjar Satrija; Yusuf Ridwan (JURNAL KAJIAN VETERINER, 2019)
This study aims to determine the effect of season on the prevalence of gastrointestinal nematode infections in beef cattle in Bojonegoro Regency. The study was conducted in the coverage area of the Sekolah Peternakan Rakyat (SPR) Mega Jaya, Kasiman District, Bojonegoro Regency. Fecal samples were taken from 263 heads cattle in the dry season and 270 headsin the rainy season. The local climatic data obtained from the One Stop Service Office of the Agency for Meteorology, Climatology and Geophysics (BMKG). Results showed significant differences in the prevalence of nematodosis between the dry season to the rainy season. Prevalence of nematodosis in the dry season by 50.98%, significantly lower than the prevalence in the rainy season, which reached 67.78%.